SYSTEMATIC STUDIES OF BORNEAN ZINGIBERACEAE: II. ELETTARIA OF SARAWAK - SAKAI, S.; NAGAMASU, H. (Edinburgh Journal of Botany, 2000)
Elettaria (Zingiberaceae) of Sarawak are studied, and eight species are recognised including four new species: E. linearicrista, E. longipilosa, E. brachycalyx and E. kapitensis. Elettaria surculosa and E. stolonifera, which have previously been included in E. multiflora, are treated as independent species. Examination of recent collections reveal that characters such as anther dehiscence patterns, form of the labellum and anther crest are taxonomically important. A key to all species of Bornean Elettaria is provided.